2011
DOI: 10.1039/c0mt00064g
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Caenorhabditis elegans on the role of metals in neurodegenerative diseases

Abstract: Neurodegeneration is characterized by the cell death or loss of structure and/or function of neurons. Many neurodegenerative diseases including Parkinson’s disease (PD) and Alzheimer’s disease (AD) are the result of neurodegenerative processes. Metals are essential for many life processes, but they are also culpable for several neurodegenerative mechanisms. In this review, we discuss the role of metals in neurodegenerative diseases with emphasis on the utility of Caenorhabditis elegans (C. elegans) genetic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 103 publications
0
26
0
Order By: Relevance
“…Uric acid can scavenge free radicals, nitrogen-oxygen-based radicals, such as peroxynitrite and its derivatives, and chelate iron [48]. In vitro and vivo studies, it is suggested that uric acid is a powerful radical scavenger of neurons [46][47][48].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Uric acid can scavenge free radicals, nitrogen-oxygen-based radicals, such as peroxynitrite and its derivatives, and chelate iron [48]. In vitro and vivo studies, it is suggested that uric acid is a powerful radical scavenger of neurons [46][47][48].…”
Section: Discussionmentioning
confidence: 98%
“…Cerebral tissue is susceptible to oxidative damage because of its high oxygen requirement for metabolism, the high level of polyunsaturated fatty acid, and the low concentration of antioxidant resources [46,47]. The effect of serum uric acid upon the Alzheimer's disease has been widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of laboratory-adapted C . elegans to toxic levels of copper sulfate was observed to reduce brood size and life span while slowing development [1820]. …”
Section: Introductionmentioning
confidence: 99%
“…elegans studies have also confirmed that manganese exposure may have an additive effect on DAergic neurodegeneration in neurons containing α-synuclein protein aggregates. Various labs have concluded that the C. elegans SMF-1 transporter, an analogue of the divalent metal transporter (DMT-1) found in humans, is important in the degeneration of these neurons [146,147,149,150]. Results in C. elegans indicate that this transporter plays a significant role in neurotoxicity by transporting manganese into the cell where it can induce numerous intracellular changes.…”
Section: Manganese-containing Dithiocarbamate Fungicidesmentioning
confidence: 99%